THE EFFECTIVENESS OF COOPERATIVE LEARNING IN DEVELOPING STUDENTS' ARGUMENTATIVE ESSAYS : A Case Study in an EFL Writing Class in a State University in Banten - Miranty, Delsa (2012)
This research investigates the effectiveness of cooperative learning in developing students' argumentative essays, primarily for fourth semester of English department students. Specifically, this research attempts to answer the questions of the chances of implementing cooperative learning principles in a writing class; the problems that occurs when teacher implementing the principles; the effect on students' argumentative essays and the response of the learners towards the cooperative learning method that applied in this research.This study employed mainly a qualitative method and descriptive analysis. The site of this study is a state university in Banten Province and the participants are its fourth semester of English department students. There were 39 students that were involved in this study. Then the students were selected and divided into three groups representing the low, the average, and the high learners. The data in this study were gathered through four main instruments: students' written texts, classroom observation, interview and questionnaires.This study reveals that, in term of chances of implementing cooperative learning, the students like to share their ideas, opinion and suggestions with other students through their argumentative essays projects with their team. It can be stated that the problem occurs since there was a fact about the condition that the students had difference in education background and length of learning English did not show a significant difference in terms of degree of mastery of requesting in the target language. It proves that cooperative learning has challenges. One of the challenges is the students' low mastery and ability in English and writing (Bryan, 1996.,Herawati, 2009). Then, the next finding reveals that the students had improvement in the writing argumentative essays both for individual quizzes and for group projects. It can be said that students made good progress during cooperative learning for their individual quizzes and group projects. And the last finding was about the responses from the students about cooperative learning that implemented in their writing class. The responds that given by the students were positive since they got many advantages when the teacher applied this method in the writing class. Based on these findings, it is recommended to supports the extensive research into academic writing that emphasizes the importance of explicit teaching of the structures of specifics written genres, particularly argumentative essays, to second-language students (Connor&Mbaye, 2002 cited in Saito, 2010:31) This is my final comment: I think that you need to simplify your abstract, since it needs compact and full statements regarding your research. Do not too much cope with technical explanations, as they are explained in your 4th chapter. Emphasize on your methods and findings.